Qualidade de vida relacionada à saúde de homens submetidos à prostatectomia radical: comparação Brasil - Espanha - Gomes, Cassia Regina Gontijo (Universidade Federal de São Carlos, 2019)
ntroduction: Prostate cancer (PC) is the third most common cancer in the general population, and the second most frequent among men from all over the world. Radical prostatectomy (RP) stands out as a therapeutic option for the localized PC. The main disadvantages of performing the surgery are the occurrence of urinary incontinence (UI) and sexual dysfunction (SD), which significantly impacts the health-related quality of life (HRQOL) of patients. Objective: To compare the HRQOL of Spanish and Brazilian men submitted to RP. Method: Multicentric, quantitative, descriptive, comparative and cross-sectional study conducted in Asturias (Spain) and Minas Gerais (Brazil). This study included patients undergoing RP after the removal of the bladder catheter and less than 24 months postoperatively. Data collection occurred through a socio-demographic, clinical and surgical characterization instrument, as well as two QOL instruments validated in Spain and Brazil, the World Health Organization Quality Life-Bref (WHOQOL-Bref) and the Expanded Prostate Cancer Composite Index (EPIC). Results: 160 prostatectomized Spanish and 165 Brazilians were evaluated. Among the participants in Spain, the averages of the scores of the general scale and of each WHOQOL-brief domain were: general (69.9), physical (80.0), psychological (79.2), social relations (63.1) and environment (88.5). In Brazil, the following averages were found: general (73.6), physical (78.0), psychological (82.2), social relations (68.0) and environment (81.1). In relation to the EPIC domains, the average values of the participants in Spain and Brazil were respectively: urinary (83.6 and 82.0), intestinal (97.0 and 98.7), sexual (31.9 and 38.6) and hormonal (90.9 and 94.5). In Spain, the aspects that most contributed to a better assessment of QOL were financial resources, access to information and opportunities for leisure activity. In Brazil, the factors that most favor a better perception of QOL by the participants were the absence of frequent feelings of bad mood, anxiety and depression, as well as a demonstration of resignation in relation to the decline in sexual function. Conclusions: In this study a better perception of HRQOL was found among Brazilian prostatectomized patients than among the Spanish.
Calidad de vida relacionada con la salud de hombres sometidos a la prostatectomía radical - comparativo Brasil-España
Keywords: Qualidade de vida relacionada à saúde; Prostatectomia; Brasil; Espanha; Health-related quality of life; Prostatectomy; Brazil; Spain; CIENCIAS DA SAUDE::ENFERMAGEM